2015
DOI: 10.1111/jsr.12356
|View full text |Cite
|
Sign up to set email alerts
|

How to measure snoring? A comparison of the microphone, cannula and piezoelectric sensor

Abstract: Summary The objective of this study was to compare to each other the methods currently recommended by the American Academy of Sleep Medicine (AASM) to measure snoring: an acoustic sensor, a piezoelectric sensor and a nasal pressure transducer (cannula). Ten subjects reporting habitual snoring were included in the study, performed at Landspitali—University Hospital, Iceland. Snoring was assessed by listening to the air medium microphone located on a patient's chest, compared to listening to two overhead air med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 32 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…The cannula has several problems that remain to be solved. In the first place, the 200 Hz sampling rate of the cannula is a limitation on the detection of snore events. Therefore, the cannula only detects frequencies up to 100 Hz as compared to the 4 KHz that the microphone can capture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cannula has several problems that remain to be solved. In the first place, the 200 Hz sampling rate of the cannula is a limitation on the detection of snore events. Therefore, the cannula only detects frequencies up to 100 Hz as compared to the 4 KHz that the microphone can capture.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there only has been a single report that has compared the three devices discussed by the AASM (i.e., nasal cannula, microphone, and piezoelectric sensor) using a few patients, but that report was based on individual snore events, expanding the sample satisfactorily. 16 The study found the microphone to be most effective. However, a comprehensive evaluation of the nasal cannula's diagnostic accuracy in snoring detection still is lacking.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We performed a full-night home-based sleep study using a T3 device (Nox Medical â , Reykjav ık, Iceland) to measure snoring and AHI (Arnardottir et al, 2015;Cairns et al, 2014). Embedded microphones recorded snoring sound (8 kHz sampling).…”
Section: Snoring and Osamentioning
confidence: 99%
“…The AASM lists three methods (microphone, nasal pressure transducer and piezoelectric vibration sensor) with no expressed preference. Arnardottir and colleagues (Arnardottir et al ., 2016b) report the well‐presented results of a simple and elegant study in which the three types of sensors are compared. The conclusion is clear: a microphone placed on the chest is the most sensitive method.…”
Section: Standards In Sleep Medicine: Respiratory Events and Snoringmentioning
confidence: 99%